Genetic Variability and Predicted Responses to Four Types of Progeny Selection in a Nigeria Maize (Zeamays L.) population. - Adeyemo, Moses Olusegun (Obafemi Awolowo University, 2014)
Genetic variability and predicted responses to full-sib (FS), half-sib (HS), Si and S1 testcross (TCH) selection methods were studied in the open-pollinating maize variety, TZSR-Y-1. Evaluation of progress after one cycle of selection was also done. Grain yield and seven agronomic traits were investigated.